(untitled) (African Journal of Biomedical Research, 2020)
Sexual activity is rampant among female undergraduates with the consequence of unintended pregnancies, abortions and sexually transmitted diseases. This study was conducted to assess the prevalence and predictors of unprotected sexual intercourse and abortion; the knowledge, access to and use of contraceptives; as well as the knowledge of and exposure to sexually transmitted Infections among undergraduates of the Polytechnic and University of Ibadan. It was a cross-sectional descriptive study that employed a multi-stage sampling method. A structured questionnaire was administered to undergraduates of the Polytechnic of Ibadan (PTI) and the University of Ibadan (UI). Data were collected on demographic profile; reproductive and sexual history; knowledge, attitude to and use of contraceptives; and knowledge of and exposure to Sexually Transmitted Infections. Analysis was done using SPSS version 15.0. Significantly more males (27% vs 18%) were sexually active and more (25%) students of PTI than UI (19%). Abortion was significantly more prevalent in the Polytechnic (5.3%) than the University (1.6%). The major reason pregnancies were aborted was that they were unplanned for and abortion seekers were not ready for consequent financial responsibilities (57%) of keeping the conceptuses. Knowledge of the various forms of contraception was poor. Males had better access to contraceptives than females and significantly more males (36%) than females (6%) used contraceptives always. Overall, self-pleasure was the single principal reason (75.4%) respondents had sexual intercourse and significantly more females (21.6%) than males (12.5%) had sex to please their partner(s). Knowledge about sexually transmitted Infections was assessed as fair